Ru, Pd doped WO3 nanomaterials: a synergistic effect of noble metals to enhance the acetone response properties - Kodam, Pavan M.; Ghadage, Pandurang A.; Nadargi, Digambar Y.; Shinde, K. P.; Mulla, Imtiaz S.; Park, J. S.; Suryavanshi, Sharad S. (Ceramics International, 2022)
Noble metals (NMs) have an enormous impact on the intrinsic properties of the metal oxides. We report the synergistic effect of Ruthenium (Ru) and Palladium (Pd) noble metals on the enhancement of gas sensing properties of pure tungsten oxide (WO3). The gas sensing material is synthesized by simple and straight forward precipitation route, and its physico-chemical analyses are determined using XRD, FESEM, TEM/HRTEM, FFT, UV-Vis, XPS, EDAX, and BET measurements. Use of the developed material as a gas sensor is evaluated using several target gases (oxidizing as well as reducing), with acetone showing the best selectivity. The noble metal doping and hence catalytic action improved the gas response qualities. The synergistic effect of Ru and Pd on WO3 gas response properties are identified, where the effect is 99.80% sensitivity, and lower response/recovery time (10 s and 2 min) at 300 degrees C operating temperature. Nonetheless, the sensors displayed better gas sensing properties even at lower operating temperatures ranging from 200 to 275 degrees C. In addition, the synergistic effect has displayed the dramatic enhancement in the sensitivity to 76.44% at barely 10 ppm acetone concentration. This particular result will undoubtedly be helpful for diagnostic purpose of diabetic patients, and a strong candidate for prospective gas sensing applications, particularly acetone.
Keywords: Acetone vapours; Precipitation route; Ru -Pd doping; synergistic effect; WO3